2017
DOI: 10.1182/blood-2017-01-761346
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade for relapsed lymphoma post–allogeneic hematopoietic cell transplant: high response rate but frequent GVHD

Abstract: Given the limited treatment options for relapsed lymphoma post-allogeneic hematopoietic cell transplantation (post-allo-HCT) and the success of programmed death 1 (PD-1) blockade in classical Hodgkin lymphoma (cHL) patients, anti-PD-1 monoclonal antibodies (mAbs) are increasingly being used off-label after allo-HCT. To characterize the safety and efficacy of PD-1 blockade in this setting, we conducted a multicenter retrospective analysis of 31 lymphoma patients receiving anti-PD-1 mAbs for relapse post-allo-HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
191
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(202 citation statements)
references
References 61 publications
(88 reference statements)
7
191
0
4
Order By: Relevance
“…In another study by Haverkos et al , 28 patients received nivolumab at the dose of 3 mg/kg and 3 patients received pembrolizumab at 200 mg/kg. Out of thirty-one, 17 patients developed GVHD (10 acute and 7 chronic cases of GVHD) (7). It is noteworthy that in both studies (Herbaux et al and Haverkos et al) a majority of patients who developed CPI related GVHD, had a prior history of GVHD (12 out of 17 cases in Haverkos et al and all the 6 cases in Herbaux et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Haverkos et al , 28 patients received nivolumab at the dose of 3 mg/kg and 3 patients received pembrolizumab at 200 mg/kg. Out of thirty-one, 17 patients developed GVHD (10 acute and 7 chronic cases of GVHD) (7). It is noteworthy that in both studies (Herbaux et al and Haverkos et al) a majority of patients who developed CPI related GVHD, had a prior history of GVHD (12 out of 17 cases in Haverkos et al and all the 6 cases in Herbaux et al ).…”
Section: Discussionmentioning
confidence: 99%
“…With this PTCy-based platform, shortened-duration IS may allow for earlier or more effective administration of preemptive therapies for relapse reduction, such as cellular immunotherapies and checkpoint inhibitors [2527]. …”
Section: Discussionmentioning
confidence: 99%
“…Herbaux et al reported that 30% (6/20) of patients experienced acute GVHD, with three patients dying from treatment‐related causes. However, in the Herbaux study, GVHD was observed only in patients with prior acute GVHD, whereas in the Haverkos report, 71% of patients who developed GVHD after PD‐1 blockade had prior acute or chronic GVHD . Additional long‐term data are needed to fully evaluate the risks and benefits of using PD‐1 inhibitor therapy after allo‐HCT.…”
Section: Recognition and Management Of Imaesmentioning
confidence: 97%
“…In both studies, prolonged survival and a high overall clinical response (overall response 77% and 95%) were observed, indicative of an activated graft‐versus‐tumor effect, but outcomes were frequently complicated by the onset of treatment‐related GVHD . Haverkos et al reported that 55% (17/31) of patients developed either acute or chronic GVHD after PD‐1 inhibition, with eight treatment‐related deaths; 94% of GVHD cases occurred after one to two doses of anti‐PD‐1 therapy. Herbaux et al reported that 30% (6/20) of patients experienced acute GVHD, with three patients dying from treatment‐related causes.…”
Section: Recognition and Management Of Imaesmentioning
confidence: 99%